Co-medication and interference testing in bioanalysis: a European Bioanalysis Forum recommendation. (October 2016) - de Zwart, Marcel; Lausecker, Berthold; Globig, Susanne; Neddermann, Daniel; Le Bras, Bruno; Guenzi, Alberto; White, Stephen; Scheel-Fjording, Marianne; Timmerman, Philip
Interference testing of co-medication in bioanalytical method validation has become an area of debate in view of the increased specificity offered by current state-of-the-art technology in both LC–MS/MS and ligand-binding assay platforms. In view of this, and considering the extensive experience within the European Bioanalysis Forum member companies, we evaluated the impact of co-medication on the performance of hundreds of bioanalytical methods with the aim of providing a science-based recommendation on how to evaluate and document potential interference from co-medication on the PK parameters in clinical studies in patients and volunteers.